Aplikasi Stop Motion Menyampaikan Informasi tentang Gizi Seimbang Kepada Publik - Suriati; Sumi Khairani (Journal of Informatics Management and Information Technology, 2024)
Video media in the field of information technology is currently used for documentation and communication. Such as video recordings, advertisements and so on can now be processed and processed using a computer. One type of video that is included in interesting animation is the stop motion method. Stop motion animation is animation that is packaged in the form of images where the objects are photographed one by one according to the movement of the object or the movement of the desired object. In this research, the stop motion method was implemented which was packaged in an application designed using the Macromedia Flash application. The Flash application will display stop motion videos that have been made and added with theoretical features about balanced nutritional information. Information about balanced nutrition will be presented in the form of a flash application, and also a stop motion video that has been created